Strategies for Sharia Tourism Management: Realizing Sustainable Halal Tourism - Agus Wahyu Irawan (Study Program of Sharia Business Management , Faculty of Islamic Economics and Business, 2024)
Halal tourism, or Sharia tourism, has emerged as a rapidly growing sector within the global tourism industry, driven by the increasing demand from Muslim travelers seeking destinations that align with their religious principles. This study explores the strategic management practices necessary to develop and sustain halal tourism while addressing challenges such as the lack of standardized guidelines, limited infrastructure, and misconceptions about Sharia tourism. By adopting a comprehensive approach that includes policy development, infrastructure investment, community engagement, and marketing innovation, halal tourism can unlock its full potential as a driver of economic growth, cultural preservation, and ethical travel. The research emphasizes the role of collaboration among governments, private sector stakeholders, and local communities in fostering an ecosystem that supports halal tourism. Furthermore, capacity-building efforts through education and training are highlighted as critical to ensuring consistent service quality. This study concludes that strategic management is key to realizing sustainable halal tourism, benefitting both Muslim and non-Muslim travelers while promoting inclusivity and cross-cultural understanding in the global tourism landscape.